The effect of oral preexposure prophylaxis on the progression of HIV-1 seroconversion. (10th September 2017) - Donnell, Deborah; Ramos, Eric; Celum, Connie; Baeten, Jared; Dragavon, Joan; Tappero, Jordan; Lingappa, Jairam R.; Ronald, Allan; Fife, Kenneth; Coombs, Robert W.
Abstract : Objective: To investigate whether oral preexposure prophylaxis (PrEP) alters timing and patterns of seroconversion when PrEP use continues after HIV-1 infection. Design: Retrospective testing of the timing of Fiebig stage HIV-1 seroconversion in the Partners PrEP Study, a randomized placebo-controlled clinical trial of PrEP conducted in Kenya and Uganda. Methods: Specimens from 138 seroconverters were collected every 3 months and when HIV-1 infection was suspected based on monthly rapid HIV-1 tests. Progression of seroconversion was compared between randomized groups (PrEP versus placebo) and per-protocol groups (placebo versus PrEP participants with detectable tenofovir during the seroconversion period) using laboratory assessment of Fiebig stage. Delay in site-detection of seroconversion and association with PrEP drug-regimen resistant virus were assessed using logistic regression. Analysis of time to each Fiebig stage used maximum likelihood estimation with a parametric model to accommodate the varying lengths of HIV-infection intervals. Results: There was a significant increase in delayed site detection of infection associated with PrEP (odds ratio = 3.49, P  = 0.044). Delay in detection was not associated with increased risk of resistance in the PrEP arm (odds ratio = 0.93, P  = 0.95). Estimated time to each Fiebig stage was elongated in seroconverters with evidence of ongoing PrEP use, significantly for only Stage 5 (28 versus 17 days, P  = 0.05). Adjusted for Fiebig stage, viral RNA was ∼2/3 log lower in those assigned to PrEP compared with placebo; no differences were found in Architect signal to cut-off at any stage. Conclusion: Ongoing PrEP use in seroconverters may delay detection of infection and elongate seroconversion, although the delay does not increase risk of resistance. Abstract : Supplemental Digital Content is available in the text